The EU in a Trans-European Space External Relations across Europe, Asia and the Middle East - Giusti, Serena; Mirkina, Irina (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XIX, 266 p. 5 illus., 1 illus. in color.